2000
DOI: 10.1128/aac.44.7.1809-1817.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Localization and Molecular Characterization of the nonS Gene Required for Macrotetrolide Biosynthesis in Streptomyces griseus DSM40695

Abstract: The macrotetrolides are a family of cyclic polyethers derived from tetramerization, in a stereospecific fashion, of the enantiomeric nonactic acid (NA) and its homologs. Isotope labeling experiments established that NA is of polyketide origin, and biochemical investigations demonstrated that 2-methyl-6,8-dihydroxynon-2E-enoic acid can be converted into NA by a cell-free preparation from Streptomyces lividans that expresses nonS. These results lead to the hypothesis that macrotetrolide biosynthesis involves a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 50 publications
2
50
0
4
Order By: Relevance
“…(3-14) Little is known about the intricate genetic, biocatalytic and mechanistic details of how enantiomeric, or pseudo-enantiomeric metabolites, are constructed. Co-isolated congeners in the same, as well as distinct oxidation states, presumably derived from the same pathway or, via parallel pathways are evident, including the biogenesis postulated by Ma.…”
mentioning
confidence: 99%
“…(3-14) Little is known about the intricate genetic, biocatalytic and mechanistic details of how enantiomeric, or pseudo-enantiomeric metabolites, are constructed. Co-isolated congeners in the same, as well as distinct oxidation states, presumably derived from the same pathway or, via parallel pathways are evident, including the biogenesis postulated by Ma.…”
mentioning
confidence: 99%
“…Molecular biological research of nonactin which consists of stereoisomeric homologues of hydroxy acid S in pamamycin, was carried by Priestley et al [18] and Shen et al [19]. We postulate that the homologue of nonS gene, which encodes the enzyme catalyzing the formation of a tetrahydrofuran ring of the constituent hydroxy acid of nonactin, exists in the pamamycin biosynthetic gene cluster.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] On the basis of these results we concluded that NonJK represented C-0 bond-forming type II PKSs that act directly on (±)-8 to catalyze their tetramerization and cyclization into 7, demonstrating the first time that PKS has the intrinsic propensity to evole catalytic activities catalyzing other than C-C bond formation ( Figure 3A). We have now co-expressed nonJK in E. coli and showed that cell-free extract made from E. coli overexpressing nonJK can efficiently catalyze the synthesis of 7 from (±)-8; no activity was detected in cell-free extracts made from E. coli carrying the expression vector as a negative control or constructs expressing nonJ or nonK alone.…”
Section: Nonjk-type II Pkss That Catalyze C-o Bond Formationmentioning
confidence: 99%